Developing and Evaluating Validity and Reliability of Persian Version of "Dichotic Fused Rhymed Word Test" - Nasrin Ghanbari; Younes Lotfi; Ahmad Reza Nazeri; Abdollah Moussavi; Saeideh Mehrkian; Enaiatollah Bakhshi; Asma Khadiv (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: The aim of the present study is to develope and evaluate validity and reliability of Persian version of Dichotic Fused Rhymed Words Test in 18-25 years old normal population. Materials & Methods: The Persian version of Dichotic Fused Rhymed Words Test consisted of 15 pairs of monosyllable rhymed words. These paired words are set in 4 lists of 30 items that simultaneously were presented one to the left and another to the right ear so that they lead to perception of a single fusion concept. After selecting the test material from Moin Persian dictionary according to the intended criteria and pairing the rhymed words, content validity was assessed through lawshe method by 10 expert persons, words with high validity were selected and lists were set. Then, the words of each list were recorded on CD in a dichotic mode. Thereafter, the study was performed in 124 normal individuals (68 females and 56 males) within ages ranging from 18 to 25 years and the scores were recorded on a designed scoring form. To examine reliability of test, the test was performed on 15 individuals again two weeks after the initial test and the Pearson correlation was assessed. Results: There are significant differences between mean scores of right and left ears (P<0.001). Content Validity Ratio was 0.8-1 for every item. Pearson correlation was 0.83 for test-retest (P<0.001). Cronbach’s alpha and Intra Class Correlation (ICC) was 0.81 and 0.84 for internal correlation between scores of lists of test. The result showed that there is significant correlation between the lists. Conclusion: Based on the obtained results, the Persian version of Dichotic Fused Rhymed Words Test has a good content validity and reliability. It can be used in detecting function of corpus callosum, lateralization of the cerebral hemispheres and assessment of central auditory processing.